2000
DOI: 10.2105/ajph.90.10.1601
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and survival following bereavement

Abstract: A B S T R A C TObjectives. This study investigated the effect of parental bereavement on cancer incidence and survival.Methods. A cohort of 6284 Jewish Israelis who lost an adult son in the Yom Kippur War or in an accident between 1970 and 1977 was followed for 20 years. We compared the incidence of cancer in this cohort with that among nonbereaved members of the population by logistic regression analysis. The survival of bereaved parents with cancer was compared with that of matched controls with cancer.Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(20 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…For instance, parents who outlive their children are more likely to have poorer self-reported health than those who do not experience the death of a child (Murphy et al, 1999). They are at higher risk of developing anxiety and depressive disorders (Kreicbergs et al, 2004), cardiovascular disease (Li et al, 2002), diabetes (Olsen et al, 2005), and certain types of cancer (Levav et al, 2000). Bereaved parents are more likely than non-bereaved parents to have suicidal thoughts (Murphy et al, 2003), to commit suicide (Chen et al, 2012), and to die earlier (Li et al, 2003; Rostila et al, 2012).…”
Section: Death Of a Child And Parental Wellbeingmentioning
confidence: 99%
“…For instance, parents who outlive their children are more likely to have poorer self-reported health than those who do not experience the death of a child (Murphy et al, 1999). They are at higher risk of developing anxiety and depressive disorders (Kreicbergs et al, 2004), cardiovascular disease (Li et al, 2002), diabetes (Olsen et al, 2005), and certain types of cancer (Levav et al, 2000). Bereaved parents are more likely than non-bereaved parents to have suicidal thoughts (Murphy et al, 2003), to commit suicide (Chen et al, 2012), and to die earlier (Li et al, 2003; Rostila et al, 2012).…”
Section: Death Of a Child And Parental Wellbeingmentioning
confidence: 99%
“…Intertwined with grief, the health consequences for parents are broad and often chronic. For example, past research has shown that parents are at risk of psychiatric hospitalization following the death of a child (Li et al 2005); increased risk of cancer (Levav et al 2000); elevated mortality (Li et al 2003); and prolonged grief that lasts indefinitely (Klass 1999; Rogers et al 2008). Each of these impacts may have secondary effects on surviving siblings.…”
Section: Background Literaturementioning
confidence: 99%
“…On the other hand, there are several case-control studies on this topic1011121330, although case-control studies are susceptible to biases. For example, cancer patients recall more stressful events than controls31, which could lead to a spurious association between psychological stress and the risk of colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a type of prospective study design has been employed in which exposure information is obtained prior to knowledge of colorectal cancer diagnosis. As such, there is a study that examined the association between bereavement and cancer incidence13. That study identified 76 and 11,602 cases of incident colorectal cancer among 6,284 Jewish parents who lost one or two sons and among 1,019,255 individuals in the Jewish general population, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation